Представление автоматов группами. II - Скобелев, В.Г. (Український математичний журнал, 2000)
Одержано необхідні та достатні умови, при яких зображення абстрактних автоматів скінченними групами погоджено з функцією переходів автомата. Одержано достатні умови, при яких відображення вільної півгрупи автомата у групу, що здійснюється компонентою зображення, є гомоморфізмом. We obtain necessary and sufficient conditions under which the representation of abstract automata in terms of finite groups is consistent with the transition function of an automaton. We obtain sufficient conditions under which the mapping of a free semigroup of an automaton into a group realized by a component of the representation is a homomorphism.